Does the histopathological subtype of primary basal cell carcinoma predict the subtype of secondary tumours? What role do genetic mutations play? - Liam D. Turner; Andrea Zarkovic; Jessica Lee Siew Hua; Weng Chan; Siddharth Ogra; Daniel Brettell; Oded Ohana; Pavindran Gounder; Mark Hayes; Simon Madge (Wiley, 2023)
Abstract Background Basal cell carcinoma (BCC) is one of the most common malignancies in the world. The frequency of histopathological subtypes and the distribution on the body of BCC has been well documented. Less has been written on the nature of secondary tumours. The genetics of BCC is starting to be understood, particularly with the advent of newer medical treatments (hedgehog inhibitors). Objectives To determine if primary basal cell carcinoma histopathological subtype predicts secondary tumour subtype, as well as their anatomical distribution. Methods A retrospective case series of patients over the age of 18 was performed from 2009 to 2014, with at least two separate diagnoses of BCC. Results In 394 identified patients, a total of 1355 BCCs arose in the cohort over the 6‐year study period. The number of secondary BCCs per patient ranged from 2 to 19 tumours. Nodular BCC was the most likely to reoccur in secondary tumours (53.3%), followed by mixed subtypes (45.7%). Conclusions Within our study, we did find a predisposition for secondary BCCs to be of the same histopathological subtype as the primary, particularly with respect to nodular and mixed tumours. Furthermore, we found that secondary tumours were also more likely to occur on the same anatomical site as the primary tumour. We are only just beginning to under the genetic mutations involved in subtype formation.